(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SUMMARY: 1. The relevant Past - 2. Protest and Print - 3. The ramist Answer - 4. Modern Minds - Two Foundations. ABSTRACT: In the global age the modern Western, secular, and material way of understanding human existence is generally accepted to provide the norm by which every alternative view is evaluated. It is the standard against which all other ways of thinking are judged. It is the accepted basis on which entire systems of law, forms of government, methods of education, and a modern way of life is extended across every region and people of the earth. Viewed historically, however, the fact that such a way of understanding should become the norm is quite ironic. Despite the predominance of this mode of thought in the present age, as far as can be determined, nearly all people who have ever lived on the earth, until very recent times, have lived according to principles and values that not only included the rational and material ways of understanding but combined them with a religious, sacred, or miraculous aspect as well. In fact, the peoples of the West were once uniformly of this mentality - and many remain so. Moreover, it was not until a great transformation began to take place, beginning around 1600 that the modern secular and materialistic way of understanding came to provide the basic premise for a Western way of life in which religious belief and spirituality survived, but mostly in an instrumental or subordinated role. The story of how this new Method of understanding - premised on Thought rather than Being, Fact rather than Truth, Empirical and Rational, rather than a fully human way of apprehending - involves three pivotal figures: Francis Bacon, Rene Descartes, and especially, Peter Ramus (Pierre de La Ramee). Following on these men an architecture of the modern mind - what Foucault called an episteme - is coming to predominate among a global population. It is a way of thinking based on some combination of their teachings. To understand how and why this occurred is to understand how and why the sacred or miraculous dimension of human existence lay outside a paradigm that shapes the global age.